SEAL wolf surrender - Spear, Terry (Sourcebooks Casablance, an imprint of Sourcebooks, 2019)
In dire need of a bodyguard, she-wolf Natalie Silverton falls under the protection of wolf shifter and Navy SEAL-turned-private investigator Brock Greystoke with whom sparks fly as they work closely together to catch the bad guys.